ChemInform Abstract: BICMAP‐Rhodium(I)‐Catalyzed Asymmetric 1, 4‐Addition of Arylboronic Acids to Coumarins. Issue 8 (February 2016) - Mino, Takashi; Miura, Kazuki; Taguchi, Hiroyuki; Watanabe, Kohei; Sakamoto, Masami
Abstract: 4‐Arylchroman‐2‐one derivatives are obtained in good yields and with high enantioselectivities.